Analisis Kekuasaan Presiden dalam Proses Pembentukan Undang-Undang Ditinjau dari Perspektif Trias Politica - Tamara Yuldha; Husein Manalu (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
In the 1945 Constitution of the Republic of Indonesia (UUD RI), Article 20 paragraph (2) states that approved bills must be passed by the President, which indicates that the President of the Republic of Indonesia has a role in the discussion of laws. In the United States, the President is not involved in the discussion of the bill, but has the right of veto to reject the bill. This aims to prevent laws that are detrimental to society. However, Article 22 of the 1945 Constitution has created a debate about the limits of the President's authority to form a Government Regulation in Lieu of Law (PERPU), especially in relation to the urgency that can be subjective. The 1945 Constitution of the Republic of Indonesia emphasizes that the House of Representatives (DPR) has the main role in the legislative and supervisory functions. This study aims to explain the power of the President in the formation of laws, taking into account the principle of Trias Politica. The President's authority to enact PERPU is based on Article 22 paragraph (1) of the 1945 Constitution, which authorizes the President in the face of compelling urgency. In addition, the process of promulgation through the promulgation stage is also emphasized by Law Number 15 of 2019 concerning the Formation of Legislation. The promulgation stage is one of the five steps in the formation of laws, after officially becoming a law, the regulation can be accessed, known, and obeyed by everyone. However, in practice, every bill submitted by the Government usually passes the discussion stage with the DPR.